Seeing Down to the Bottom: Nondestructive Inspection of All‐Polymer Solar Cells by Kelvin Probe Force Microscopy. Issue 18 (8th July 2016) - Cui, Zequn; Sun, Jianxia; Landerer, Dominik; Sprau, Christian; Thelen, Richard; Colsmann, Alexander; Hölscher, Hendrik; Ma, Wanli; Chi, Lifeng
Abstract : The material composition in a bulk heterojunction (BHJ) of an all‐polymer solar cell is analyzed down to the bottom surface by Kelvin probe force microscopy. The phase separation of the composites both on the top and at the bottom of a BHJ can be measured and reconstructed with this easy‐to‐use approach in a nondestructive way.